Prevalence of diabetes mellitus and its predictors among tuberculosis patients currently on treatment - Deepak Sharma; Naveen Krishan Goel; Munish Kumar Sharma; Dinesh Kumar Walia; Meenal Madhukar Thakare; Rajiv Khaneja (Wolters Kluwer Medknow Publications, 2018)
Background: Tuberculosis (TB) and diabetes are the world's leading public health issues. They are the cause of morbidity, mortality, and pose a burden on the healthcare system. Aims and Objectives: The aim and objective of this study were to study the prevalence of diabetes and its predictors among TB patients currently on treatment. The secondary objective was to examine the self-reported blood glucose monitoring and antidiabetic drug adherence practice among diabetic TB patients. Methodology: This cross-sectional study was undertaken on 275 TB cases enrolled from selected designated microscopy centers. Self-reported information on diabetes, tobacco usage, and family history of TB was collected by trained investigators. In addition, for diabetic tubercular patients, the study investigators inquired about the type of treatment taken (allopathic/traditional), frequency of getting blood sugar tested, and daily drug adherence. For comparison between the "diabetes TB comorbidity" and "TB only group," Chi-square test of significance was used, and odds ratios were reported. Data were analyzed using Epi Info software (CDC Atlanta). Results: The prevalence of diabetes among TB patients was found to be 13.1% (known diabetics -9.1% and new diabetics -4.0%). There were 25.5% of current/former smokers (70/275) and 13.1% of current/former smokeless tobacco users (36/275). In logistic regression analysis, age 50 years and above emerged as a significant predictor for diabetes TB comorbidity (adjusted odds ratio = 9.8 [4.3-22.3]). Conclusion: Diabetes is prevalent comorbidity in TB patients. Age more than 50 years significantly increases the odds of this twin morbidity.